Was Anna Schwartz right? The role of government size and the exchange rate regime for macroeconomic stability - Philipp Wegmueller (University of Bern, Department of Economics, 2014)
I contribute to the resurging debate on the reform of the international monetary system by asking: How does the size of the public sector under different exchange rate regimes affect macroeconomic stability and welfare? In response to a meeting of the Bretton Woods Commission in 1993, renowned economist Anna Schwartz (2000) claimed providently that the increasing size of the public sector impedes the viability of an exchange rate regime with a fixed rule for convertibility. I study her line of reasoning using a new Keynesian small open economy framework. One important feature of the paper is to bridge the literature on the choice of the exchange rate regime with the literature on the effects of government size for macroeconomic stability. The main findings are threefold: First, output is stabilized by the share of the public sector and destabilized by the tax rate, irrespective of the exchange rate regime in place. Second, inflation is destabilized by the level of income taxes under flexible prices but stabilized under sticky prices. Finally, irrespective of the model specification, an exchange rate peg exhibits the largest macroeconomic volatility and highest welfare losses.
Keywords: E32; E52; E63; F33; 330; Exchange Rate Regimes; Government Size; Welfare; Macroeconomic stability